Behçet's syndrome as a tool to dissect the mechanisms of thrombo‐inflammation: clinical and pathogenetic aspects. (18th December 2018) - Becatti, M.; Emmi, G.; Bettiol, A.; Silvestri, E.; Di Scala, G.; Taddei, N.; Prisco, D.; Fiorillo, C.
Summary: Behçet's syndrome (BS) is a complex disease with different organ involvement. The vascular one is the most intriguing, considering the existence of a specific group of patients suffering from recurrent vascular events involving the venous and, more rarely, the arterial vessels. Several clinical clues suggest the inflammatory nature of thrombosis in BS, especially of the venous involvement, thus BS is considered a model of inflammation‐induced thrombosis. Unique among other inflammatory conditions, venous involvement (together with the arterial one) is currently treated with immunosuppressants, rather than with anti‐coagulants. Although many in‐vitro studies have suggested the different roles of the multiple players involved in clot formation, in‐vivo models are crucial to study this process in a physiological context. At present, no clear mechanisms describing the pathophysiology of thrombo‐inflammation in BS exist. Recently, we focused our attention on BS patients as a human in‐vivo model of inflammation‐induced thrombosis to investigate a new mechanism of clot formation. Indeed, fibrinogen displays a critical role not only in inflammatory processes, but also in clot formation, both in the fibrin network and in platelet aggregation. Reactive oxygen species (ROS)‐derived modifications represent the main post‐translational fibrinogen alterations responsible for structural and functional changes. Recent data have revealed that neutrophils (pivotal in the pathogenetic mechanisms leading to BS damage) promote fibrinogen oxidation and thrombus formation in BS. Altogether, these new findings may help understand the pathogenetic bases of inflammation‐induced thrombosis and, more importantly, may suggest potential targets for innovative therapeutic approaches. Abstract : Thrombotic events in BS are sustained by an inflammatory process rather than a thrombophilic state. Reactive oxygen species (ROS)‐derived modifications represent the main post‐translational fibrinogen alterations responsible for structural and functional changes. Neutrophils (pivotal in the pathogenetic mechanisms leading to BS damage) promote fibrinogen oxidation and thrombus formation in BS.